The Influence of Hospital Management Service Quality Toward Doctors Satisfaction in JKN Era at Dumai City Public Hospital (RSUD Dumai) - Yossi, Irma (Universitas Ubudiyah Indonesia, 2018)
Dumai City Public Hospital (RSUD Dumai), is one of the local government-owned hospitals in Riau Province that has been serving JKN patients. The doctors stated that since the era of JKN the workload of doctors become more severe because of the large number of patients who must be served with high working hours, Then social jealousy between doctors who have been efficient to serve patients with doctors who are still relatively wasteful in providing services because it does not affect the amount of medical services accepted so as if there is no sanction against such wasteful doctors so it affects doctorsâ satisfaction in working. The purpose of this study is to determine and analyze the influence of hospital management service quality toward doctors satisfaction in JKN era at Dumai city Public Hospital (RSUD Dumai). This type of research is a survey research with explanatory research approach that aims to explain about the influence of hospital management service quality to doctorsâ satisfaction. Subjects in this study were all functional doctors in Dumai City General Hospital amounted to 51 people. The results showed the quality of hospital management service statistically consisted of physical evidence dimension (Tangibles) with p value = 0,001, reliability (Reability) with value of p <0,001, Responsiveness with value p <0,001, Assurance with value p <0.001 and attention (empathy) with p value <0.001, have a significant effect on doctorsâ satisfaction. Physical evidence dimension (Tangibles) has the greatest effect on the satisfaction with the value of the coefficient (B) 0,552. The result of this research is the quality of hospital management service consists of physical evidence dimension (tangibles), reliability, responsiveness, assurance and attention (empathy) affect doctorsâ satisfaction in JKN era at Dumai City Public Hospital (RSUD). The most influential service quality is the Physical Evidence (tangibles).influence on doctorsâ satisfaction in JKN era at Dumai City Public Hospital (RSUD Dumai). The most influential service quality is the Physical Evidence (Tangibles).Â It is suggested to the hospital party to try to meet the expectations of doctors through improving the quality of service based on the quality of hospital management services dimension in order to improve doctorsâ satisfactionKeywords: service quality, doctors satisfaction